Spontaneous Regression of Multiple Emphysematous Bullae - Hiroaki Satoh; Tokihiko Suyama; Yuko T Yamashita; Morio Ohtsuka; Kiyohisa Sekizawa (Canadian Respiratory Journal)
The etiology of emphysematous bullae is not well known; thus, the management of bullous lung disease is often difficult because of concomitant underlying emphysema and coexisting cardiac conditions. The present paper reports a case in which near complete resolution of multiple emphysematous bullae in the right lung occurred spontaneously. This case is of interest, not only because of the rarity with which spontaneous regression of multiple emphysematous bullae has been reported in the literature, but also because of the accompanying dramatic improvements in radiological results and pulmonary function of the patients.